2009
DOI: 10.1002/aoc.1594
|View full text |Cite
|
Sign up to set email alerts
|

New chiral phosphinite ligands with C2‐symmetric axis and their possible applications in Ru‐catalyzed asymmetric transfer hydrogenation

Abstract: Following activation by NaOH, these chiral ruthenium complexes serve as catalyst precursors for the asymmetric transfer hydrogenation of acetophenone derivatives in iPrOH. The complexes 3 and 4 showed high catalytic activity but low selectivity in asymmetric transfer hydrogenation reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…It is known that the catalytic efficiency of hemilabile phosphine derivative PN ligands increases in the catalytic reactions of Ru(II) complexes. This is because in complex structures the soft ruthenium metal coordinates with the soft phosphorus and the hard nitrogen acts as an efficient catalyst …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the catalytic efficiency of hemilabile phosphine derivative PN ligands increases in the catalytic reactions of Ru(II) complexes. This is because in complex structures the soft ruthenium metal coordinates with the soft phosphorus and the hard nitrogen acts as an efficient catalyst …”
Section: Introductionmentioning
confidence: 99%
“…This is because in complex structures the soft ruthenium metal coordinates with the soft phosphorus and the hard nitrogen acts as an efficient catalyst. [13][14][15] In this article, we report the synthesis of Ru(II) complexes with iminophosphines. These complexes were used as catalysts in the reduction of derivatives of styrenes and ketones in homogeneous catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that the novel half‐sandwich complexes, based on ligands with PN and PO backbone, are active catalysts in the reduction of aromatic ketones . The observed activity of these complexes has encouraged us to examine other analogous ligands and their ruthenium complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported the synthesis of new P,O-ligands [21,22] and their application in ruthenium-catalyzed transfer hydrogenation reactions [23e25]. As an extension of the ongoing research program, we become interested in the synthesis of new unsymmetric ligands: (2R)-2-[benzyl{(2-((diphenylphosphanyl)oxy)ethyl)}amino] butyldiphenylphosphinite, 1 and (2R)-2-[benzyl{(2-((dicyclohexylphosphanyl)oxy)ethyl)}amino]butyldicyclohexylphosphinite, 2.…”
Section: Introductionmentioning
confidence: 99%